Method development and validation for multi-component analysis of lamivudine & tenofovir disoproxil fumarate in bulk drug by UV-visible spectrophotometer & RP-HPLC - Shweta Sharma; Amar Deep Ankalgi; Pooja Kaushal; M. S. Ashawat (Creative Pharma Assent, 2020)
A novel, simple, precise and accurate method developed for the estimation of Lamivudine and tenofovir disoproxil fumarate (TDF) in bulk drug form has been established. Lamivudine and tenofovir are well known drugs and used in treatment of HIV- Ⅰ. The method was performed by using   C18 column, ODS Hypersil column with UV detection at 262nm by using Acetonitrile and water in ratio 55:45. The retention time was found to be 2.8 and 6.8 min for Lamivudine and tenofovir disoproxil fumarate (TDF). The linearity was found in range of 6- 14µg/ml for Lamivudine and 10- 50µg/ml for Tenofovir disoproxil fumarate with flow rate 1ml/min. the method was validated for linearity, accuracy, precision and robustness as per ICH guidelines. This method is suitable for simultaneous analysis for both the nucleoside analog reverse- transcriptase inhibitors